The Association of an Alpha-2 Adrenergic Receptor Agonist and Mortality in Patients With COVID-19 - Hamilton, John L.; Vashi, Mona; Kishen, Ekta B.; Fogg, Louis F.; Wimmer, Markus A.; Balk, Robert A. (Frontiers in Medicine, 2022)
There is a need for treatments to reduce coronavirus disease 2019 (COVID-19) mortality. Alpha-2 adrenergic receptor (α2 AR) agonists can dampen immune cell and inflammatory responses as well as improve oxygenation through physiologic respiratory parameters. Therefore, α2 AR agonists may be effective in reducing mortality related to hyperinflammation and acute respiratory failure in COVID-19. Dexmedetomidine (DEX) is an α2 AR agonist used for sedation. We performed a retrospective analysis of adults at Rush University System for Health hospitals between March 1, 2020 to July 30, 2020 with COVID-19 requiring invasive mechanical ventilation and sedation (n = 214). We evaluated the association of DEX use and 28-day mortality from time of intubation. Overall, 28-day mortality in the cohort receiving DEX was 27.0% as compared to 64.5% in the cohort that did not receive DEX (relative risk reduction 58.2%; 95% CI 42.4-69.6). Use of DEX was associated with reduced 28-day mortality on multivariable Cox regression analysis (aHR 0.19; 95% CI 0.10-0.33; p < 0.001). Adjusting for time-varying exposure to DEX also demonstrated that DEX was associated with reduced 28-day mortality (aHR 0.51; 95% CI 0.28 to 0.95; p = 0.03). Earlier DEX use, initiated < 3.4 days from intubation, was associated with reduced 28-day mortality (aHR 0.25; 95% CI 0.13-0.52; p < 0.001) while later DEX use was not (aHR 0.69; 95% CI 0.27-1.50; p = 0.30). These results suggest an α2 AR agonist might reduce mortality in patients with COVID-19. Randomized control trials are needed to confirm this observation.